Advanced Yoga Mat / Fatin Raihanah Naimem - Naimem, Fatin Raihanah (2020)
In this current situation, people are likely to get involve in entertainment or find entertainment to entertain themselves. It is including of exercising while listening to music. To fulfil the demand, I came out with the idea of Advanced Yoga Mat. I focus on the athletes, sports person and public who get involve in physical activity especially yoga and strength exercise. Therefore, we have designed the product suitable to customer needs. Plus, the Advanced Yoga Mat have many advantages as it can boost our moods and emotions while exercise. It also portable which it comes with waterproof bag. Since the bag that we served is waterproof, so the speaker and the Bluetooth device will not have damage in case the bag expose to water. Next, it can be used to read the heartbeat and it can be used and suitable for all ages. It has the automatic recorded audio. We are using the high-quality battery and the device are rechargeable. Furthermore, we provide the affordable price with high quality material and provide long lasting product. We also provide a great function of our yoga mat. Other than that, we implement with interesting design which the yoga mat comes with a lot of colors that will attract people to buy.